Decomposition of drug mixture in Fenton and photo-Fenton processes: Comparison to singly treatment, evolution of inorganic ions and toxicity assay. (May 2015) - Giri, Ardhendu Sekhar; Golder, Animes Kumar
Highlights: Slightly lower decomposition of CHPL, CIP and DIPY in their mixture than singly both in FP and PFP. Cl − and F − addition caused reduction in CHPL and CIP cleavage due to suppression of release of the same heteroatoms. Mixed drug system yielded more higher molecular weight intermediates. Equimolar (0.05 mM) mixture of drugs exhibited more than 50% death of E. coli . Abstract: The degradation of three pharmaceutical compounds i.e. chloramphenicol (CHPL), ciprofloxacin (CIP) and dipyrone (DIPY) singly and from equimolar (CCD) mixture has been investigated in Fenton and photo-Fenton processes. Drug mineralization was slightly less when present singly than their mixture. The degradation efficiency was likely hindered due to formation of common ions like Cl −, F −, NH4 + and NO3 − . Addition of the same ions i.e. Cl − and F − in drug solution released upon cleavage of CHPL and CIP in CCD mixture suppressed the decomposition efficiency remarkably in both the oxidation processes. The major intermediates appeared in the mass spectra in combination of ion chromatograph were used to validate the routes of CCD decomposition and evolution inorganic ions. Furthermore, the bacterial toxicity assay was investigated using Escherichia coli ( E. coli ). The average reduction in cell death was about 38% in CCD system compared to 52%, 42% and 47% for CHPL, CIP and DIPY, respectively.